Putting Effort Into Infant Cognition. (April 2020) - Kaldy, Zsuzsa; Blaser, Erik
Working memory allows people to manipulate information in support of ongoing tasks and provides a work space for cognitive processes such as learning, reasoning, and decision making. How well working memory works depends, in part, on effort. Someone who pays attention at the right time and place will have better memory and improved performance on memory tasks. In adult cognitive research, participants' devotion of maximal task-focused effort is often taken for granted, but in infant studies, researchers cannot make that assumption. In this article, we showcase how pupillometry can provide an easy-to-obtain physiological measure of cognitive effort that allows us to better understand infants' emerging abilities. In our work, we use pupillometry to measure trial-by-trial fluctuations of effort, establishing that, just as in adults, such fluctuations influence how well infants can encode information in visual working memory. We hope that by using physiological measures such as pupil dilation, there will be a renewed effort to investigate the interaction between infants' attentive states and cognition.